The natural history of insomnia in the Ibadan study of ageing (2011)
"Study Objectives: To determine the incidence and risk factors for insomnia among an under-studied population of elderly persons in Sub-Saharan Africa. Setting: Eight contiguous predominantly Yoruba-speaking states in south-west and north-central Nigeria representing about 22% of the national population. Participants: 1307 elderly community-dwelling persons, aged 65 years and older. Measurements: Face-to-face assessment with the Composite International Diagnostic Interview, version 3 (CIDI.3) in 2007 and 12 months later in 2008 to determine the occurrence and risk factors of incident and persistent insomnia, defined as syndrome or symptom. Results: The incidence of insomnia syndrome in 2008 at 12 months was 7.97% (95% CI, 6.60–9.60), while that of insomnia symptom was 25.68% (22.68-28.66). Females were at elevated risk for both syndrome and symptom. Among persons with insomnia symptom or syndrome at the base line, 47.36% (95% CI 43.07–51.68) continued to have it one year later. Decreasing economic status was associated with increasing incidence of insomnia. Persons with chronic medical conditions at baseline were at increased risk for new onset of insomnia. Compared to persons with the lowest body mass index (BMI) (< 18.5), those with higher BMI were at elevated risk for persistence of their insomnia, with those in the obese range (≥ 30) having a 4-fold risk. Conclusions: There is a high incidence and chronicity of insomnia in this elderly population. Persons with chronic health conditions are particularly at risk of new onset as well as persistence of insomnia. "